1994
DOI: 10.1177/0148607194018006471
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Enhances Immunoregulation of Tumor Growth

Abstract: These data indicate that oral Gln supplementation, through support of host Gln stores and glutathione production, may decrease tumor growth by enhancing NK cell activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 25 publications
0
54
0
2
Order By: Relevance
“…There is a small but intriguing literature demonstrating that increased oral intakes of glutamine, administered at 1 g/kg/d in most studies, markedly slow the growth (by about 40%) of a range of transplanted tumors-a sarcoma, the MTF-7 breast cancer, and Morris hepatoma 7777-in rats while also suppressing the induction of breast cancer with DMBA; the effect on DMBA carcinogenesis was exerted at the promotional stage. [94][95][96][97] These benefits were associated with a marked increase in NK cytotoxicity; it was suspected that this was at least partially responsible for the observed tumor retardation. NK cells, like other lymphocytes, make prominent use of glutamine as an energy substrate and precursor for nucleotides, but whether this explains the observed marked impact on NK cytotoxicity is unclear.…”
Section: Boosting Immune Defenses: Focus On Natural Killer Cellsmentioning
confidence: 99%
“…There is a small but intriguing literature demonstrating that increased oral intakes of glutamine, administered at 1 g/kg/d in most studies, markedly slow the growth (by about 40%) of a range of transplanted tumors-a sarcoma, the MTF-7 breast cancer, and Morris hepatoma 7777-in rats while also suppressing the induction of breast cancer with DMBA; the effect on DMBA carcinogenesis was exerted at the promotional stage. [94][95][96][97] These benefits were associated with a marked increase in NK cytotoxicity; it was suspected that this was at least partially responsible for the observed tumor retardation. NK cells, like other lymphocytes, make prominent use of glutamine as an energy substrate and precursor for nucleotides, but whether this explains the observed marked impact on NK cytotoxicity is unclear.…”
Section: Boosting Immune Defenses: Focus On Natural Killer Cellsmentioning
confidence: 99%
“…Consideráveis esforços são realizados na identificação de substâncias capazes de melhorar a resposta imune, com os chamados imunonutrientes 3,4 . A imunonutrição constitui um novo campo de investigação em nutrição 4 .…”
Section: N T R O D U ç ã Ounclassified
“…In rats with solid tumors Austgen et al [4] did not demonstrate an increase in tumor size or DNA content, but the ratio of tumor cells to host infiltrating cells appeared to be increased. Fahr et al [8] found that tumor growth was decreased after Gln supplementation, owing to the dominant enhancement of natural killer cell activity. Gln even seems to enhance the selectivity of antitumor chemotherapy, in particular of methotrexate [19], or provide protection against doxorubicin-induced cardiotoxicity [6].…”
Section: Discussionmentioning
confidence: 99%